GABARAPs regulate PI4P-dependent autophagosome:lysosome fusion - Wang, Hanzhi; Sun, Hui-Qiao; Zhu, Xiaohui; Zhang, Li; Albanesi, Joseph; Levine, Beth; Yin, Helen (Proceedings of the National Academy of Sciences - PNAS, 2015)
Significance Autophagy is an essential homeostatic process that is critically important for maintaining health and that is dysregulated in multiple devastating diseases. The steps in the final stages of autophagy that culminate in autophagosome:lysosome fusion are not well understood. The γ-aminobutyric acid receptor-associated protein (GABARAP) family of Atg8 (autophagy-related 8) proteins has been implicated in autophagosome maturation. Here we report that phosphatidylinositol 4-kinase IIα (PI4KIIα), a lipid kinase that generates phosphatidylinositol 4-phosphate (PI4P) and binds GABARAPs, is recruited to autophagosomes by GABARAPs. Furthermore, PI4P generation by PI4KIIα, but not by PI4KIIIβ, another major mammalian PI4K, promotes autophagosome fusion with lysosomes. Our results establish for the first time to our knowledge that PI4KIIα is a specific downstream effector of GABARAP and that PI4P has a key role in the final stage of autophagy. The Atg8 autophagy proteins are essential for autophagosome biogenesis and maturation. The γ-aminobutyric acid receptor-associated protein (GABARAP) Atg8 family is much less understood than the LC3 Atg8 family, and the relationship between the GABARAPs’ previously identified roles as modulators of transmembrane protein trafficking and autophagy is not known. Here we report that GABARAPs recruit palmitoylated PI4KIIα, a lipid kinase that generates phosphatidylinositol 4-phosphate (PI4P) and binds GABARAPs, from the perinuclear Golgi region to autophagosomes to generate PI4P in situ. Depletion of either GABARAP or PI4KIIα, or overexpression of a dominant-negative kinase-dead PI4KIIα mutant, decreases autophagy flux by blocking autophagsome:lysosome fusion, resulting in the accumulation of abnormally large autophagosomes. The autophagosome defects are rescued by overexpressing PI4KIIα or by restoring intracellular PI4P through “PI4P shuttling.” Importantly, PI4KIIα’s role in autophagy is distinct from that of PI4KIIIβ and is independent of subsequent phosphatidylinositol 4,5 biphosphate (PIP ₂) generation. Thus, GABARAPs recruit PI4KIIα to autophagosomes, and PI4P generation on autophagosomes is critically important for fusion with lysosomes. Our results establish that PI4KIIα and PI4P are essential effectors of the GABARAP interactome’s fusion machinery.